2017
DOI: 10.1007/978-3-319-66399-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Data Exfiltration from Speakerless Air-Gapped Computers via Covert Hard-Drive Noise (‘DiskFiltration’)

Abstract: Air-gapped computers are disconnected from the Internet physically and logically. This measure is taken in order to prevent the leakage of sensitive data from secured networks. In the past, it has been shown that malware can exfiltrate data from air-gapped computers by transmitting ultrasonic signals via the computer's speakers. However, such acoustic communication relies on the availability of speakers on a computer.In this paper, we present 'DiskFiltration,' a covert channel which facilitates the leakage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Hanspach introduced a method called acoustical mesh networks in air, which enables the transmission of data via high frequency sound waves [13]. Guri et al also presented Fansmitter [3] and DiskFiltration [14], two methods enabling the exfiltration of data via sound waves, even when the computers are not equipped with speakers or audio hardware. This research showed how to utilize computer fans and hard disk drive actuator arms to generate covert sound signals.…”
Section: A Electromagnetic Magnetic Acoustic and Thermalmentioning
confidence: 99%
“…Hanspach introduced a method called acoustical mesh networks in air, which enables the transmission of data via high frequency sound waves [13]. Guri et al also presented Fansmitter [3] and DiskFiltration [14], two methods enabling the exfiltration of data via sound waves, even when the computers are not equipped with speakers or audio hardware. This research showed how to utilize computer fans and hard disk drive actuator arms to generate covert sound signals.…”
Section: A Electromagnetic Magnetic Acoustic and Thermalmentioning
confidence: 99%
“…Guri et al [33] utilized the HDD's built-in thermal sensors to receive data transmitted over the machine's heat emissions. Guri et al [1] used the movements of a hard drive's actuator arm to generate audible emissions that were used to exfiltrate data from airgapped machines. Since the head of a hard drive is made up of magnetic materials, the movement of the head can produce a sufficiently strong magnetic field that can be detected by a smartphone's magnetic field sensors.…”
Section: Hard Drive Covert and Side Channelsmentioning
confidence: 99%
“…Magnetic HDDs remain common [1] because of the long tail of legacy systems and the relatively inexpensive cost for high capacity storage. However, sudden movement can damage the hard drive or corrupt data because of the tight operating constraints on the read/write head(s) and disk(s).…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the transmitting computer does not need to be equipped with audio hardware or an internal or external speaker. Guri et al also presented DiskFiltration a method that uses the acoustic signals emitted from the hard disk drive (HDD) moving arm to exfiltrate data from air-gapped computers [28].…”
Section: E Acousticmentioning
confidence: 99%